Re‐evaluation of locust bean gum (E 410) as a food additive in foods for infants below 16 weeks of age and follow‐up of its re‐evaluation as a food additive for uses in foods for all population groups. (9th February 2023) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Degen, Gisela; Engel, Karl‐Heinz; Fowler, Paul J; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Husøy, Trine; Manco, Melania; et al.
Abstract: Locust bean gum (E 410) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to that assessment, the Panel on Food Additives and Flavourings (FAF) was requested to assess the safety of locust bean gum (E 410) for its uses as a food additive in food for infants below 16 weeks of age belonging to food category 13.1.5.1 (Dietary foods for infants for special medical purposes and special formulae for infants). In addition, the FAF Panel was requested to address the issues already identified during the re‐evaluation of the food additive when used in food for the general population, including the safety assessment for FC 13.1.5.1 and 13.1.5.2 (Dietary foods for babies and young children for special medical purposes as defined in directive 1999/21/EC). The process involved the publication of a call for data. Based on the received data, the Panel concluded that the technical data provided by the interested business operators support an amendment of the specifications for locust bean gum (E 410) laid down in Commission Regulation (EU) No 231/2012. The Panel identified a reference point of 1, 400 mg/kg bw per day based on reduced blood zinc levels in a piglet study. It applied the margin of exposure (MoE) for the safety assessment of locust bean gum (E 410) when used as a food additive in FC 13.1.5.1 and 13.1.5.2. The Panel concluded that a MoE above 1 would not raise a safety concern. A MoE above 1 was obtained for some of the scenarios and exposure levels for infants. For toddlers (consumers only of food for special medical purposes), the MoE was above 1 for all exposure levels.